Conservation tillage and diversified cropping enhance system productivity and eco-efficiency and reduce greenhouse gas intensity in organic farming - Babu, Subhash; Singh, Raghavendra; Avasthe, Ravikant; Rathore, Sanjay Singh; Kumar, Sanjeev; Das, Anup; Layek, Jayanta; Sharma, Vikas; Wani, Owais Ali; Singh, Vinod Kumar (Frontiers in Sustainable Food Systems, 2023)
Environmental pollution, resource dwindling, and soil degradation questioned the sustainability of contemporary agricultural production systems. Organic farming is advocated as a sustainable solution for ensuring food security without compromising environmental sustainability. But poor farm productivity quizzed the sustainability of organic production systems. Hence, a field study was carried out in the Sikkim region of the Indian Himalayas to assess the efficacy of conservation effective tilling and diversified cropping on the system productivity, profitability, environmental footprint, and soil nutrient balance in organic farming. Three tillage systems viz., i) conventional tillage(CT), ii) reduced tillage (RT), and iii) Zero tillage (ZT) and four maize diversified cropping systems [maize–black gram–toria, maize–black gram–buckwheat, maize–rajmash–toria and maize–rajmash–buckwheat were tested in three times replicated split-plot design. The NT system recorded 13.5% and 3.5% higher system productivity over CT and RT, respectively. Of the diversified cropping, the maize–rajmash–buckwheat recorded maximum system productivity (13.99 Mg ha-1) and net returns (3141 US ha-1) followed by maize–black gram–buckwheat. Among the tillage practices, NT recorded the significantly high eco-efficiency index (EEI; 1.55 US per kg CO2eq emission) and the lowest greenhouse gas intensity (GHGI; 0.15 kg CO2eq per kg production). Of the diversified cropping, maize-rajmash-buckwheat registered the lowest GHGI (0.14 CO2eq per kg production) and the highest EEI (1.47 US per kg CO2eq emission). Concerning soil nutrient balance, after three cropping cycles, the soil under NT recorded significantly higher available N (340.0 kg ha-1), P (16.6 kg ha-1), and K (337.3 kg ha-1) over the CT system at 0-10 cm soil depth. Similarly, the soil under the maize–black gram–buckwheat system had the maximum bio-available NPK. Thus, the study suggests that the cultivation of maize– black gram/rajmash-–buckwheat under NT and/or RT would increase farm productivity, profitability, and soil fertility with minimum GHGIin organic farming under the eastern Himalayan region of India.